Strategi Komunikasi Politik PKS dalam Mempertahankan Konstituen di Jawa Barat Melalui Instagram - Refi Gilang Maulana; Yusa Djuyandi (Journal of Social and Policy Issues, 2023)
The political contest that PKS participated in got good results in West Java. Maintaining constituents is the first step in winning political contestation. Instagram is one of the social media that is widely used by the people of Indonesia, it can be a forum for PKS in carrying out its political communication strategy. The research was conducted using a qualitative case study method, with interview data collection techniques through primary and secondary data sources. The results of this study are that the political communication strategy that has been carried out by the West Java DPW PKS using social media Instagram is quite structured. Be it in terms of resources or workflow. The use of Instagram social media DPW PKS West Java is under the responsibility of the public relations division, below which it is divided into several deputies. Messages conveyed on Instagram can be in the form of pictures or videos, in substance they can be in the form of socio-political issues that are currently developing in society or publication of party agendas. In creating content on Instagram, there are several paths. Kesimpulan The conclusion of this study is that Instagram content is tailored to the target segmentation, namely young people. The evaluation was carried out by the West Java PKS DPW by conducting a manual report. PKS national public relations evaluation has an event called PR Summit.